Dinosaur! : dinosaurs and other amazing prehistoric creatures as you've never seen them before - Woodward, John, frey50; Naish, Darren; Minister, Peter; Lewis, Arran; Kerr, Andrew; Bull, Peter, 1960-; Konstantinov, Vlad (London Dorling Kindersley Limited, 2014)
Brings the extraordinary animals of prehistory to life, using the latest in digital technology. Take a journey through the Triassic, Jurassic, and Cretaceous worlds to discover giant predatory reptiles lurking in the seas, pterosaurs the size of small planes soaring through the skies, and colossal dinosaurs striding over the land. Meet the monstrous mammals that cam next, such as the saber-toothed Smilodon and the wooly mammoth. Computer-generated imagery reveals the scales, spikes, teeth, and talons of these curious creatures.
Life on Earth -- Animals with backbones -- What is a dinosaur? -- Dinosaur diversity -- Life in the Mesozoic -- Triassic life. The Triassic World -- Nothosaurus -- Placerias -- Eoraptor -- Postosuchus -- False alarm -- Plateosaurus -- Eudimorphodon -- Isanosaurus -- Coelophysis -- Jurassic life. Jurassic World -- Megazostrodon -- Heterodontosaurus -- Scelidosaurus -- Cryolophosaurus -- Stenopterygius -- Monolophosaurus -- Liopleurodon -- Anchiornis -- Allosaurus attack -- Rhamphorhynchus -- Kentrosaurus -- Diplodocus -- Pterodactylus -- Stegosaurus -- Allosaurus -- Giraffatitan -- Archaeopteryx -- Cretaceous life. The Cretaceous World -- Iguanodon -- Sinosauropteryx -- Repenomamus -- Hypsilophodon -- Confuciusornis -- Psittacosaurus -- Muttaburrasaurus -- Pterodaustro -- Sauropelta -- Alarm calls -- Spinosaurus -- Argentinosaurus -- Pteranodon -- Velociraptor -- Albertonectes -- Struthiomimus -- Citipati -- Therizinosaurus -- Deinosuchus -- Nemegtbaatar -- Euoplocephalus -- Parasaurolophus -- Saltasaurus -- Mosasaurus -- Edmontosaurus -- Pachycephalosaurus -- Quetzalcoatlus -- Triceratops -- Tyrannosaurus -- A new era. The Cenozoic World -- Titanoboa -- Gastornis -- Icaronycteris -- Uintatherium -- Darwinius -- Forest threat -- Andrewsarchus -- Carcharodon megalodon -- Megatherium -- Smilodon -- Woolly mammoth.
Includes index.
Keywords: Dinosaurs; Extinct animals; Juvenile works; Pictorial works